Teachers’ perception, plan, implementation and assessment of Letterland in teaching English vocabulary - Istifadah, Hanna; Anggani Linggar Bharati, Dwi (Universitas Negeri Semarang, 2020)
Letterland is a child-friendly, multi-sensory system to teach English for children. It is highly a sophisticated teaching technique that combines stories with pictograms of letters. However, many teachers claimed to have difficulties in implementing it properly. This study aimed to investigate how teachers perceived, planned, implemented and assessed Letterland in teaching English vocabulary and analyzed the alignment and misalignment of teachers’ perception, plan, implementation and asessment of Letterland. A case study as a part of qualitative research design was employed in this study. By using purposeful sampling technique, two English teachers from Star Kiddy Preschool Semarang were involved. There were four instruments to collect the data, namely questionnaire, interview, document analysis and classroom observation. The findings of this study revealed that the English teachers had positive responses to questionnaire data and interview data dealing with Letterland and its implementation. In addition, Letterland designed well in lesson plan by teachers. Nevertheless, Letterland technique was conducted less succesfully in the classroom. This was due to several problems such as limited time, lack of preparation and teachers’ lack of creativity. Furthermore, as the implementation of teacher’s assessment, it has already met the standard of assessment on curriculum PAUD 2013. At last, the alignment of those teachers’ perception, plan and assessment toward Letterland were related to each other. Eventhough teacher’s positive perception did not align with their implementation in the classroom. That was because teachers missed some stages that should be added in the classroom.